2021
DOI: 10.1093/gbe/evaa267
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Comparisons of Ergot Fungi Reveals the Divergence and Evolution of Species within the Genus Claviceps Are the Result of Varying Mechanisms Driving Genome Evolution and Host Range Expansion

Abstract: The genus Claviceps has been known for centuries as an economically important fungal genera for pharmacology and agricultural research. Only recently have researchers begun to unravel the evolutionary history of the genus, with origins in South America and classification of four distinct sections through ecological, morphological, and metabolic features (Claviceps sects. Citrinae, Paspalorum, Pusillae, and Claviceps). The first three sections are additionally characterized by narrow host range, while sect. Cla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 107 publications
3
39
1
11
Order By: Relevance
“…Our data shows that TE are significantly close to PSP in the two analyzed C. paspali isolates. This difference between our report and previous reports for RRC-1481 [ 74 ] could be due the difference in structural annotations used for analysis and prediction method for PSP. Also, PSP in ILB432 (and not in ILB388) were found to be significantly closer to LTRs compared with other genes.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Our data shows that TE are significantly close to PSP in the two analyzed C. paspali isolates. This difference between our report and previous reports for RRC-1481 [ 74 ] could be due the difference in structural annotations used for analysis and prediction method for PSP. Also, PSP in ILB432 (and not in ILB388) were found to be significantly closer to LTRs compared with other genes.…”
Section: Discussioncontrasting
confidence: 96%
“…It has been reported that PSP could be located in more repeat-rich regions and TE could be associated with the loss or gain of a particular gene responsible for rapid evolution, including gain and loss of pathogenicity-related genes in these isolates [i.e: 84, 85, 97, 98]. In Claviceps genus there are reports of this in Claviceps and Pusillae sections [ 74 ]. Our data shows that TE are significantly close to PSP in the two analyzed C. paspali isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In many filamentous pathogens, effector genes are enriched in TE-rich and gene-sparse compartments, whereas they are typically underrepresented in TE-poor and gene-dense genomic regions that typically harbor housekeeping genes ( Seidl and Thomma 2014 ; Dong et al 2015 ; Frantzeskakis et al 2020 ). TE-rich compartments are often characterized by increased substitution rates and increased occurrence of SVs and presence/absence polymorphisms ( Raffaele et al 2010 ; Croll and McDonald 2012 ; de Jonge et al 2012 , 2013 ; Dutheil et al 2016 ; Hartmann and Croll 2017 ; Hartmann et al 2017 ; Wang et al 2017 ; Fokkens et al 2018 ; Plissonneau et al 2018 ; Grandaubert et al 2019 ; Gan et al 2021 ; Wyka et al 2021 ). Notably, a similar association of TEs with genes involved in immune responses has also been observed in plant hosts ( Leister 2004 ; Kawakatsu et al 2016 ; Mascher et al 2017 ; Seidl and Thomma 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The 37 genome sequences assembled in this study resulted in 1362 to 2581 contigs, N50 values ranged from 19,946 to 55,909 bp, and the completeness measured by Benchmarking Universal Single-Copy Orthologs (BUSCO) over the fungal database (fungi odb10) ranged from 97% to 99.1% (Table 1, available in GenBank https://www.ncbi.nlm.nih.gov/ (accessed on 9 November 2021) as accessions JAIURI000000000-JAIUSS000000000 available upon publication of the article). The quality of the assemblies was equivalent to the assemblies of 17 genomes from previous studies (Table 1) [44,45]. Overall, the 54 assemblies of 53 strains (two versions of assemblies for CCC1102 were included because certain genes were obtained from one or the other assemblies) of 19 Claviceps species included in this study belong to three sections: C. sect.…”
Section: Genome Assembliesmentioning
confidence: 99%
“…Moreover, all three strains of C. quebecensis had a second partial nonfunctioning copy of easE (275, 275, and 1208 bp) and two partial copies of easF with good open reading frames (ORFs), and they were lacking easH2 (Table 2). * The assembly versions: BW was from Wingfield et al [45], SW was from Wyka et al [44], and WF was generated in the present study; values in the cells denote contig numbers; the 2nd contig number was led by a/when the fragment is on two contigs; green color represents full-length genes, light orange represents partial or gapped sequences, and no fill represents no gene matches; hatches denote fragments containing frameshifts or internal stop codons. None of the genes were detected in C. citrina (C. sect.…”
Section: Ergot Alkaloid Genes (Eas)mentioning
confidence: 99%